Political and legal aspects regarding Romania’s participation in the Second World - Stefan Gheorghe (Journal of Danubian Studies and Research, 2022)
Romania’s participation in the Second World War was determined by political considerations and strategic needs, generated by the evolution of the international political situation in the middle of the twentieth century. The loss of an area of about 1/3 of the national territory and 6 million inhabitants, in favor of the three neighbors of the Romanian state, respectively the Soviet Union, Hungary and Bulgaria will be the fundamental reason for Romania’s participation in military operations on both fronts. east and west, of the second world conflagration.